Divergence of flowering-related genes to control flowering in five Euphorbiaceae genomes - Jiang, Lan; Fan, Tingting; Wang, Lihu; Zhang, Lin; Xu, Jun (Frontiers in Plant Science, 2022)
Reproductive growth and vegetative growth are a pair of main contradictions in the process of plant growth. Flowering, as part of reproductive growth, is a key switch in the life cycle of higher plants, which affects the yield and economic benefits of plants to a certain extent. The Euphorbiaceae species, including castor bean (Ricinus communis), physic nut (Jatropha curcas), tung tree (Vernicia fordii), cassava (Manihot esculenta), and rubber tree (Hevea brasiliensis), have important economic values because they are raw materials for the production of biodiesel, rubber, etc. The flowering mechanisms are still excluded in the Euphorbiaceae species. The flowering-related genes of Arabidopsis thaliana (Arabidopsis) were used as a reference to determine the orthologs of these genes in Euphorbiaceae genomes. The result showed that 146, 144, 114, 114, and 149 of 207 A. thaliana genes were respectively matched to R. communis, V. fordii, J. curcas, H. brasiliensis, and M. esculenta. These identified genes were clustered into seven pathways including gibberellins, floral meristem identity (FMI), vernalization, photoperiod, floral pathway integrators (FPIs), and autonomous pathways. Then, some key numbers of flowering-related genes are widely conserved in the Euphorbiaceae genomes including but not limited to FPI genes LFY, SOC1, FT, and FMI genes AG, CAL, and FUL. However, some genes, including FRI, FLC, and GO, were missing in several or all five Euphorbiaceae species. In this study, we proposed the putative mechanisms of flowering-related genes to control flowering and provided new candidate flowering genes for using marker-assisted breeding to improve variety quality.